Supplementation of extract of Lafoensia pacari in the diet of semi heavy laying hens - Janaina da Silva Moreira; José Henrique Stringhini; Edemilson Cardoso da Conceição; Emmanuel Arhnold; Raiana Almeida Noleto; Fabyola Barros de Carvalho (Acta Scientiarum. Animal Sciences, 2017)
It was intended to evaluate the supplementation of Lafoensia pacari standardized in tannins extract in the diet of laying hens on the performance, internal and external quality of eggs and metabolism of the feed nutrients. A total of 168 Isa Brown laying hens, aged 24 weeks, with the mean weight of 2.6 kg and the mean posture rate of 87% were used during 4 periods of 28 days each. The treatments consisted of Halquinol performance-enhancing antibiotic, Mannanoligosaccharide (MOS) prebiotic and three levels of pacari extract – 1,000, 2,000 and 3,000 mg kg-1of feed. The experimental design was completely randomized, with six treatments and seven replicates of four hens each. The pacari standardized in tannin extract presented a percentage of albumen and an egg weight similar to the antibiotic (p < 0.04). The supplementation with the extract improved the shell quality, verified by the specific gravity (p < 0.03) and promoted the metabolizability of ether extract similar to antibiotic and MOS (p < 0.04), allowing its indication as a phytogenic additive.